The relationship between m-banking service quality and loyalty: evidence in Indonesian Islamic Banking - Rizaldi Yusfiarto (Asian Journal of Islamic Management (AJIM), 2021)
Purpose: This study generally aims to comprehensively examine the effect of mobile banking service quality on creating customer loyalty in Islamic banking. In particular, this research uses the E-S-Qual instrument to verify service quality in mobile banking and uses one mediation variable, namely e-customer satisfaction. Methodology: This study amounted to 273 Islamic banking customers. The total participants are divided into several categories such as; gender, occupation, domicile, and Islamic bank used. The data obtained were analyzed using the Structural Equation Modeling (SEM) approach. This study also uses a second-order perspective (reflective-reflective) SEM on the E-S-Qual variable (efficiency, fulfillment, system availability, and privacy), then the approach used refers to the repeated indicators. Findings: The higher mobile banking service quality has implications for customer loyalty, both attitude and behavior. It happens when the customer is satisfied with the quality of the system displayed. This satisfaction can be achieved if the dimensions of quality that are characteristic of the system can be presented by Islamic banking.Originality: This study underscores the dimensions of efficiency and system availability as keys to mobile banking service quality. Efficiency refers to how the ease, accessibility, and speed provided by the system can facilitate transactions and other functions. Furthermore, system availability refers to how the platforms function properly in relation to technical constraints that may arise, as well as attachment to functions that strengthen processes in the business of Islamic banking customers.